Knowledge of nurses at a psychiatric hospitalization unit of a teaching hospital Saberes de los enfermeros en una unidad de internación psiquiátrica en un hospital universitario Saberes dos enfermeiros em uma unidade de internação psiquiátrica de um hospital universitário - Agnes Olschowsky; Maria de Lourdes Custódio Duarte (Universidade de São Paulo, 2007)
This study aims to identify the knowledge of the nurses in a psychiatric hospitalization unit at a university hospital. It is an exploratory, descriptive research with a qualitative approach, utilizing semistructured interviews. The nurses refer to a change in the assisting care, starting from their experience in the asylum mode and making references to the concepts of the psychosocial mode: integrality, welcoming, interdisciplinarity and interpersonal relationship. Integral and individual care, knowledge of the psychiatric syndromes and their treatment as well as the consideration of the subjectivity of the subject under psychiatric suffering are part of the knowledge that guides nursing actions in mental health. Este estudio tiene por objetivo identificar los saberes de los enfermeros en una unidad de internación psiquiátrica en un hospital universitario. Se trata de una investigación exploratoria, descriptiva, con aproximación cualitativa, utilizando la entrevista semi-estructurada. Los enfermeros refieren una transformación en el cuidado asistencial a partir de su experiencia en el modo asilar, haciendo referencias a las concepciones del modo psicosocial: integralidad, acogida, interdisciplinaridad y relación interpersonal. El cuidado integral e individual, el conocimiento de los síndromes psiquiátricos y su tratamiento y la consideración de la subjetividad del individuo bajo sufrimiento psíquico son formas del saber que orientan las acciones de la enfermería en salud mental. Este estudo tem o objetivo de identificar os saberes dos enfermeiros em uma unidade de internação psiquiátrica em um hospital universitário. Trata-se de pesquisa exploratório-descritiva, com abordagem qualitativa, utilizando a entrevista semi-estruturada. Os enfermeiros relatam transformação no cuidado assistencial a partir de sua experiência no modo asilar, fazendo referências às concepções do modo psicossocial: integralidade, acolhimento, interdisciplinaridade e relacionamento interpessoal. O cuidado integral e individual, o conhecimento sobre as síndromes psiquiátricas e seu tratamento e a consideração da subjetividade do indivíduo, em sofrimento psíquico, são saberes que norteiam as ações de enfermagem em saúde mental.